Aplicação da medida de segurança de internação aos portadores de transtornos mentais, em face do princípio da dignidade da pessoa humana: o caso da cidade Rio Branco-AC (2005-2010) - Oliveira, Rivana Barreto Ricarte de (2012)
The great revolution of humanity, in a global perspective, is the affirmation of the human being as the center of decision of the collective organization. The development of this knowledge culminates with the notion that human dignity is a reflection of the moral progress that consists recognizing in the person an inherent value around which are structured social and political organizations, that do not allow any distinction or discrimination between human beings, even if they are sane or mentally ill people. Supported by this context, the present work analyzes the way the precautionary action is implemented and executed towards mental health patients in Rio Branco-AC, in the period of 2005 to 2010, demonstrating the current execution system of this action in front of the human dignity principle. Kant s conception of human dignity was taken as a reference to develop the dignity of the mentally insane, taking the concept of autonomy in its abstract view, the individual s potential capacity to self-determine their conduct, regardless of their actual implementation by the person in concrete. The history of madness based on Foucault was seen in order to understand the process of insanity criminalization, revisiting aspects of the emergence of psychiatry and the psychiatric hospital itself. Discussion is held on the Brazilian penal system, emphasizing the consolidation of precautionary action as the institute that promotes the exclusion of the inclusion of the mentally disordered people. Emphasis is given to the psychiatric reform movement that has made feasible relevant changes to the mental health legislation and has also subsidized, although at an embryonic stage, alternative programs of treatment to the insane offender. Through the analysis of court proceedings, institutions and the interviews realized, it was possible to obtain concrete information about the current situation of the mentally ill patients who committed a criminal unjust, in Rio Branco, and verify the violations of the basic rights of citizenship, health and dignity. The research results show a need for deep reflection on the naturalization of the noted violations, since the legal process related to madness appears subverted in the whole extension of its practical application, demonstrating the paradoxes between practice and theoretical discourse. Finally, it poins to the crucial need for readjustments to the policy of implementation and application of the precautionary action in the city of Rio Branco- AC.